Changes in Hydrocodone Misuse Exposures Reported to U.S. Poison Centers Following Rescheduling in 2014. (7th June 2022) - Fischer, Laura J.; Severtson, Stevan G.; Gurrola, Marie C.; Iwanicki, Janetta L.; Green, Jody L.; Dart, Richard C.
Abstract: Background: In 2014, the Drug Enforcement Administration rescheduled hydrocodone combination products to Schedule II to reduce nonmedical use and diversion. Methods: The impact of rescheduling was assessed using quarterly data from 2011 through 2019 from the Researched Abuse, Diversion and Addiction-Related Surveillance (RADARS ® ) System Poison Center Program and IQVIA TM Longitudinal Prescription Data. Trends and immediate changes in prescriptions dispensed and misuse exposures before and after rescheduling involving hydrocodone, oxycodone, and other Schedule II opioid analgesics were calculated using segmented regression. Results: Hydrocodone prescriptions were stable pre-rescheduling, decreased by 2.7% (95% CI: −3.6%, −1.8%, p < 0.0001) per quarter post-rescheduling. Misuse exposures involving hydrocodone were decreasing by 3.2% (95% CI: −3.9%, −2.4%, p < 0.0001) per quarter pre-rescheduling and decreased by 4.9% (95% CI: −5.5%, −4.2%, p < 0.0001) post-rescheduling. Immediate decreases in hydrocodone prescriptions and misuse exposure rates in 2014Q4 compared to 2014Q3 were significant and different from oxycodone or other Schedule II opioids. Schedule II opioid analgesics prescriptions in aggregate were stable prior to rescheduling, decreased by 10.8% (95%CI: −14.0%, −7.6%, p < 0.0001) immediately after the rescheduling, and decreased by 2.3% per quarter (95% CI: −3.1%, −1.5%, p < 0.0001) subsequently. Misuse exposures involving these opioids were decreasing by 3.3% (95% CI: −4.1%, −2.5%, p < 0.0001) prior to rescheduling then by 2.8%, (95% CI: −3.4%, −2.2%, p < 0.0001) after rescheduling. The immediate change in misuse was not significant. Conclusions: Rescheduling corresponded with changes in hydrocodone prescribing and misuse not offset by increases in other Schedule II opioid analgesics. Misuse exposures for hydrocodone and comparators were decreasing prior to rescheduling with little change post-intervention.